All together now : creating middle-class schools through public school choice - Kahlenberg, Richard D. (Century Foundation Bks., 2001)
Annotation "In All Together Now, Richard D. Kahlenberg offers a provocative idea for improving public education: give every American child the right to attend a school in which the majority of students come from middle-class homes." "Kahlenberg combines Mann's nineteenth-century concept of the common school - which calls for educating disadvantaged and advantaged children under one roof - with the current enthusiasm for choice among public schools. This new concept, common school choice, would allow families to choose the best school for their children from a number of middle-class public institutions."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved